Contributions of Immune Cells and Stromal Cells to the Pathogenesis of Systemic Sclerosis: Recent Insights - Dai, Bingying; Ding, Liqing; Zhao, Lijuan; Zhu, Honglin; Luo, Hui (Frontiers in Pharmacology, 2022)
Systemic sclerosis (SSc) is a multisystem rheumatic disease characterized by vascular dysfunction, autoimmune abnormalities, and progressive organ fibrosis. A series of studies in SSc patients and fibrotic models suggest that immune cells, fibroblasts, and endothelial cells participate in inflammation and aberrant tissue repair. Furthermore, the growing number of studies on single-cell RNA sequencing (scRNA-seq) technology in SSc elaborate on the transcriptomics and heterogeneities of these cell subsets significantly. In this review, we summarize the current knowledge regarding immune cells and stromal cells in SSc patients and discuss their potential roles in SSc pathogenesis, focusing on recent advances in the new subtypes by scRNA-seq.